2017
DOI: 10.1155/2017/8326361
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Phylogenetics of Black Rhinoceros in Kenya in relation to Southern Africa Population

Abstract: Black rhinoceros (Diceros bicornis) are highly endangered due to poaching and other anthropological reasons and their protection to rebound the numbers and genetic improvement are necessary remedial measures defined by Rhino International Union of Conservation for the Nature Red List (IUCN). In Kenya black rhino numbers declined from approximately 20,000 in the 1970s to fewer than 400 in 1982. Wildlife conservation managers effected strategies to manage/breed the remaining rhinoceros populations in Eastern and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Our finding showed moderate bootstrap values of the maximum likelihood tree ( Figure 1); this may be because of the overall high degree of relationship among Kenyan black rhinos (Moodley et al, 2017). The low to moderate bootstrap values are consistent with those reported in a previous mitochondrial DNA D-Loop study of black rhinos (Githui et al, 2017). Although some bootstrap values were low, the populations consistently clustered into the same grouping in the tree.…”
Section: Relationships and Genetic Structuresupporting
confidence: 89%
See 2 more Smart Citations
“…Our finding showed moderate bootstrap values of the maximum likelihood tree ( Figure 1); this may be because of the overall high degree of relationship among Kenyan black rhinos (Moodley et al, 2017). The low to moderate bootstrap values are consistent with those reported in a previous mitochondrial DNA D-Loop study of black rhinos (Githui et al, 2017). Although some bootstrap values were low, the populations consistently clustered into the same grouping in the tree.…”
Section: Relationships and Genetic Structuresupporting
confidence: 89%
“…DNA extraction, amplification and sequencing procedures were similar to those in our previous study; for details see Githui et al (2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a search of Genbank, no additional Tanzanian samples were available other than those described in Moodley et al (2017); all six of the Tanzanian haplotypes identified here had been found in other East African populations in that study. However, two additional studies reported samples from Kenya (Muya et al 2011;Githui et al 2017) but without the date of sampling, so these were considered as "unclassified" . This allowed a more extensive assessment of the relative frequency of East African haplotypes in a broader context (Supplementary Table S1; Figure 5).…”
Section: Phylogenetic Context Of Tanzanian Haplotypesmentioning
confidence: 99%
“…In previous years , a total of 23 black rhinoceroses were translocated to Tanzania from areas outside East Africa but this was done without consideration of genetic variation (Fyumagwa & Nyahongo 2010). Only three haplotypes (haplotypes 3, 5 and 6) were found Githui et al 2017;Moodley et al 2017). However, the three introduced haplotypes were closely related and clustered together on the tree, suggesting that the previous translocations achieved limited augmentation of genetic diversity in the extant populations.…”
Section: Phylogenetic Context Of Tanzanian Haplotypesmentioning
confidence: 99%